Backstage Staff Communication: The Effects of Different Levels of Visual Exposure to Patients. (July 2020) - Lim, Lisa; Kanfer, Ruth; Stroebel, Robert J.; Zimring, Craig M.
Objective: This article examines how visual exposure to patients predicts patient-related communication among staff members. Background: Communication among healthcare professionals private from patients, or backstage communication, is critical for staff teamwork and patient care. While patients and visitors are a core group of users in healthcare settings, not much attention has been given to how patients' presence impacts staff communication. Furthermore, many healthcare facilities provide team spaces for improved staff teamwork, but the privacy levels of team areas significantly vary. Method: This article presents an empirical study of four team-based primary care clinics where staff communication and teamwork are important. Visual exposure levels of the clinics were analyzed, and their relationships to staff members' concerns for having backstage communication, including preferred and nonpreferred locations for backstage communication, were investigated. Results: Staff members in clinics with less visual exposure to patients reported lower concerns about having backstage communication. Staff members preferred talking in team areas that were visually less exposed to patients in the clinic, but, within team areas, the level of visual exposure did not matter. On the other hand, staff members did not prefer talking in visually exposed areas such as corridors in the clinic and visually exposed areas within team spaces. Conclusions: Staff members preferred talking in team areas, and they did not prefer talking in visually exposed areas. These findings identified visually exposed team areas as a potentially uncomfortable environment, with a lack of agreement between staff members' preferences toward where they had patient-related communication.